Communicative Managerial and Transformative Think at PT LAZ Coal Indonesia - Harnanda Eko Rusdyawan; Harliantara Harliantara; Yenny Yenny; Nurannafi Farni Syam Maella (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The coal mining business has numerous challenges, including environmental concerns and volatile market situations. PT LAZ Coal Indonesia, a prominent participant in this industry, has been in the forefront of managing these intricacies. This study aims to analyze the company's crisis management strategies, leadership approaches, and initiatives to foster sustainability. The study's theoretical approach is grounded in the principles of systems thinking in sustainability management, as elucidated in recent research. Furthermore, the study examines the significance of proficient communication and cooperative leadership in times of crisis, as highlighted in industry reports and scholarly publications. This study utilizes Robert K. Yin's case study research design and includes a combination of qualitative and quantitative data collection methods. We perform comprehensive interviews with essential staff members, scrutinize internal documents and reports, and closely examine the company's operations and decision-making procedures. The study's findings emphasize that PT LAZ Coal Indonesia's successful crisis management and sustainability activities are a direct outcome of its all-encompassing approach. The company's efficient managerial strategy, which places emphasis on transparent communication, engaging stakeholders, and collaborating to resolve issues, has played a pivotal role in effectively tackling complex obstacles. Furthermore, the organization's progressive methodology, which integrates environmental, social, and governance (ESG) elements into its strategic planning, has positioned it as a leader in the industry's sustainability endeavors. The results obtained from this particular investigation can offer significant insights for other companies operating in the coal mining industry, as well as those in allied sectors facing comparable challenges. The study's findings highlight the importance of cultivating a culture that places a high priority on communication, adaptability, and innovation, all motivated by a commitment to sustainability. This is essential for enhancing the ability of a business to withstand and recover from challenges, as well as guaranteeing its long-term sustainability.